Tingkat Keramahan Alat Tangkap Ikan Jaring Tarik Berkantong di Pelabuhan Perikanan Nusantara Tegalsari - Yulandhita Sofia Lailatul Mazidah; Yusrudin Yusrudin; Sumaryam Sumaryam (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Tegal possesses substantial capture fisheries potential, supported by the availability of adequate human resources and appropriate infrastructure. One of the most commonly utilized fishing gears at the Tegalsari Nusantara Fishing Port is the pocket seine net. This study was conducted to evaluate the environmental friendliness of pocket seine fishing gear operated by fishermen at the Tegalsari Nusantara Fishing Port and to analyze the composition of the catch produced by this gear. The research employed a survey method using a questionnaire instrument based on nine criteria for environmentally friendly fishing gear. The respondents in this study were fishermen operating pocket seine net, and the number of respondents was determined using the Slovin formula. Data were processed using descriptive analysis. Meanwhile, the catch composition data were analyzed using the comparative method. The results of the fishing gear friendliness assessment indicate that the pocket seine gear used by fishermen at the Tegalsari Nusantara Fishing Port falls within the environmentally friendly category, with an indicator score ranging from 19 to 27. The catch composition of pocket seine gear comprises 12 species, which are classified into main catch and bycatch. All captured species possess economic value; consequently, no catch is discarded.